Decision tree model-based cost-effectiveness analysis of ligation for prolapsed hemorrhoids versus Ruiyun procedure for hemorrhoids for grade Ⅱ to Ⅲ prolapsed hemorrhoids - Yang Haibo; Shi Zhan; Chen Wei; Ding Peilin; Wang Jiandong (结直肠肛门外科)
[Objectives] To evaluate the cost-effectiveness of ligation for prolapsed hemorrhoids versus Ruiyun procedure for hemorrhoids for grade Ⅱ to Ⅲ prolapsed hemorrhoids. [Methods] A cost-effectiveness model was built on a randomized controlled trial conducted at the Putuo Hospital Affiliated to Shanghai University of Traditional Chinese Medicine between May 2018 and June 2021. In this trial, 66 patients with grade Ⅱ to Ⅲ prolapsed hemorrhoids were randomly assigned to the treatment group (n=33, receiving ligation for prolapsed hemorrhoids) and the control group (n=33, receiving Ruiyun procedure for hemorrhoids). Costs of hospitalization, and clinical data such as effectiveness were collected. A decision tree model was built with the Treeage Pro 2011. Model outputs included quality adjusted life years (QALYs), cost-effectiveness ratio (CER), and incremental cost-effectiveness ratio (ICER). One-way sensitivity analyses and probabilistic sensitivity analyses were performed. [Results] Cure rate was significantly higher in the treatment group than in the control group (P < 0.05). Compared to the control group, the treatment group had significantly lower hospitalization costs (P < 0.05) but similar QALYs gains (P > 0.05). CER in the treatment group was significantly lower than that in the control group (P < 0.05), indicating ligation for prolapsed hemorrhoids is more cost-effective. ICER was-119, 019.6 RMB/QALYs, indicates that the treatment group has a cost-effectiveness advantage. Sensitivity analyses showed similar results to base-case model results. [Conclusion] Compared with Ruiyun procedure for hemorrhoids, ligation for prolapsed hemorrhoids has a cost-effectiveness advantage. It has certain value of clinical promotion.